2019
DOI: 10.3892/ol.2019.10733
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and functional analyses of key genes in smoking‑associated lung adenocarcinoma

Abstract: Smoking is one of the most important factors associated with the development of lung cancer. However, the signaling pathways and driver genes in smoking-associated lung adenocarcinoma remain unknown. The present study analyzed 433 samples of smoking-associated lung adenocarcinoma and 75 samples of non-smoking lung adenocarcinoma from the Cancer Genome Atlas database. Gene Ontology (GO) analysis was performed using the Database for Annotation, Visualization and Integrated Discovery and the ggplot2 R/Bioconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In other cancers, bioinformatic studies using the Human Genome Atlas has identified NTS as a clinically significant differentially expressed gene in determining survival in oral squamous cell carcinoma [32]. NTSR1 mRNA expression appeared to be an important survival factor in smoking-associated lung adenocarcinoma [33]. Additionally, NTS has been identified as a hub differentially expressed gene in recurrence of lower-grade brain glioma [34].…”
Section: Discussionmentioning
confidence: 99%
“…In other cancers, bioinformatic studies using the Human Genome Atlas has identified NTS as a clinically significant differentially expressed gene in determining survival in oral squamous cell carcinoma [32]. NTSR1 mRNA expression appeared to be an important survival factor in smoking-associated lung adenocarcinoma [33]. Additionally, NTS has been identified as a hub differentially expressed gene in recurrence of lower-grade brain glioma [34].…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, smokers and nonsmokers were accurately identi ed in LA based on a support vector machine (SVM) classi cation model constructed from 27 characteristic genes with signi cant enrichment of cancer proteoglycan and Ras signaling pathway [24] . It was suggested that 7 mRNAs including CYP17A1, PKHD1L1, RPE65, NTSR1, FETUB, IGFBP1 and G6PC might be used as prognostic indicators in smokers with LA [9] . However, very few researchers focus on the development from normal lung tissue to LA tissue in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it was found that aberrant activation of mast cells and CD4 + memory T cells also contributed to LA development and progression. However, the signaling pathways and driver genes in smoking-associated lung adenocarcinoma remain uncertain [9] . In the last few decades, we mainly focused on the effect of smoking between lung cancer patients and normal people.…”
Section: Introductionmentioning
confidence: 99%
“…The functional features of the CMT-related genes were examined by R software [ 20 , 21 ] and KOBAS 3.0 [ 22 , 23 ]. To understand the CMT-related genes underlying biological processes, Gene Ontology analyses (GO; http://geneontology.org ) were conducted using R software (version 3.6.2).…”
Section: Methodsmentioning
confidence: 99%